Pengaruh Komsumsi Coklat Hitam Terhadap Tingkat Nyeri Dismenore Primer Pada Remaja Putri di Pondok Pesantren Tanwiriyyah Kab. Cianjur Tahun 2023 - Sofie Chaliani; Rina Afrina; Siti Kamillah (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
Dysmenorrhea is pain during menstruation in the lower abdomen and waist caused by an increase in prostaglandins, which cause the uterus to contract rapidly. In Indonesia, the incidence of primary dysmenorrhea is 55%. Primary dysmenorrhea causes many young women to be unable to participate in learning. One way to treat primary dysmenorrhea is by consuming dark chocolate. Dark chocolate contains magnesium, calcium, potassium, theobromine, which can block the production of prostaglandins so that it can reduce pain during menstruation. This researcher aims to determine the effect of consuming dark chocolate on the level of primary dysmenorrhea pain in young women at the Tanwiryyah Islamic boarding school, Cianjur Regency. This research uses a quasi-experimental design with a one group pretest-posttest design. The population in the study was 70 people with a sample of 20 people. The results of the study showed that there was an influence of dark chocolate consumption on the level of primary dysmenorrhea pain with a 2-tailed significant value of 0.000 <0.005, so it was concluded that there was an influence of dark chocolate consumption on the level of primary dysmenorrhea pain in young women at the Tanwiryyah Islamic boarding school, Cianjur district. It is hoped that teenagers can use alternative dark chocolate consumption to reduce the level of dysmenorrhea.